Lack of evidence for prognostic value of epidermal growth factor receptor intron‐1 CA repeats for oral carcinomas. (2nd February 2017) - Precht, Clarissa; Blessmann, Marco; Kluwe, Lan; Scheld, Theresa; Schön, Gerhard; Henningsen, Anders; Pflug, Christina; Smeets, Ralf; Heiland, Max; Gröbe, Alexander
Abstract : Epidermal growth factor receptor (EGFR) expression is altered in several malignancies, including oral squamous cell carcinoma. A CA‐repeat polymorphism in intron‐1 (CA‐SSR‐1) of the EGFR gene is reported to influence EGFR expression and is associated with features of various solid tumors and outcomes of cancer patients. In the present study we evaluated the influence of length and zygosity of CA‐SSR‐1 on the survival of patients with oral squamous cell carcinoma. The length and zygosity of CA‐SSR‐1 was obtained through microsatellite analysis in 91 patients with oral cancer, who were treated in the Department of Oral and Maxillofacial Surgery of the University Medical Centre Hamburg Eppendorf, Germany, during the years 1998–2008. Follow up was conducted until 2016. Outcome measures were age, gender, tumor stage, occurrence of metastases, and date of recurrence or death. Statistical analysis was conducted using the chi‐square test and the log‐rank test. Neither length nor zygosity of the CA‐SSR‐1 in patients with oral squamous cell carcinoma was significantly correlated with sex, age, tumor size, tumor localization, lymph node involvement, metastasis status, disease‐free survival, or overall survival. Length and zygosity of the CA‐SSR‐1 polymorphism in EGFR is not able to serve as a prognostic biomarker in White European patients with oral squamous cell carcinoma.